Penapisan Isolat Rizobakteri Indigenos untuk Pengendalian Ganoderma boninense pada Bibit Kelapa Sawit (Elaeis guineensis Jacq.) - Yanti, Yulmira; Arnetti, Arnetti; Rifai, Imam (Politeknik Negeri Lampung, 2019)
Basal stem rot (Ganoderma boninense) is one of the main diseases of oil palm. The objective of the research was to obtain indigenous rhizobacteria (RBI) isolate which have the ability increase growth and to control basal stem rot on oil palm seedlings in planta. Experimental research consists of 3 stages by using Completely Randomized Design (CRD). Indigenous rhizobacteria isolate testing as plant growth promoting rhizobacteria (PGPR) and to control of G. boninense on pre-nursery of oil palm consisted of 29 treatments (27 RBI isolates, without G. boninense inoculation as positive control, and G. boninense inoculation as negative control) with 5 replications each. Data were analyzed by variance, if the result significantly different, it was continued by using Least Significance Different (LSD) at 5% level. The results showed that two of the best isolates were RZ2E 2.1 and RZ2E 1.2 which were able to increase growth and were able to suppress the development of basal stem rot G. boninense.